2016
DOI: 10.1002/chem.201600294
|View full text |Cite
|
Sign up to set email alerts
|

Montecrinanes A–C: Triterpenes with an Unprecedented Rearranged Tetracyclic Skeleton from Celastrus vulcanicola. Insights into Triterpenoid Biosynthesis Based on DFT Calculations

Abstract: Three new triterpenoids with an unprecedented 6/6/6/6-fused tetracyclic carbon skeleton, montecrinanes A-C (1-3), were isolated from the root bark of Celastrus vulcanicola, along with known D:B-friedobaccharanes (4-6), and lupane-type triterpenes (7-12). The stereostructures of the new metabolites were elucidated based on spectroscopic (1D and 2D NMR) and spectrometric (HR-EIMS and HR-ESIMS) techniques. Their absolute configurations were determined by both NMR spectroscopy, with (R)-(-)-α-methoxyphenylacetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In this study, all species and organs analyzed presented this type of secondary metabolites. Previous studies reported pentacyclic and tetracyclic triterpenes from Salvadoran Celastraceae species, including M. chiapensis [34], Crossopetalum uragoga [35], C. xylocarpa, [36] and C. vulcanicola [37], and those isolated from M. chiapensis [34] and C. vulcanicola [37] represented unprecedented tetracyclic D:B-friedobaccharane, and montecrinane skeletons, respectively. Coumarins represent a class of aromatic secondary metabolites derived from the shikimic acid pathway, which have a wide variety of biological activities [38].…”
Section: Phytochemical Analysismentioning
confidence: 97%
“…In this study, all species and organs analyzed presented this type of secondary metabolites. Previous studies reported pentacyclic and tetracyclic triterpenes from Salvadoran Celastraceae species, including M. chiapensis [34], Crossopetalum uragoga [35], C. xylocarpa, [36] and C. vulcanicola [37], and those isolated from M. chiapensis [34] and C. vulcanicola [37] represented unprecedented tetracyclic D:B-friedobaccharane, and montecrinane skeletons, respectively. Coumarins represent a class of aromatic secondary metabolites derived from the shikimic acid pathway, which have a wide variety of biological activities [38].…”
Section: Phytochemical Analysismentioning
confidence: 97%
“…The triterpenoids most commonly isolated from Celastraceae species are pentacyclic and belong to the lupane, oleane, friedelane, taraxerane, glutinane, and ursane series . The tetracyclic triterpenes such as dammaranes, D:B‐friedobaccharane, and montecrinanes are unusual triterpenes in this family. The basic molecular skeleton of dammarane triterpenoids consists of a tetracyclic framework and a side chain moiety; these compounds have attracted worldwide attention due to their potent bioactivities, such as antitumor, anti‐inflammatory, immunostimulatory, neuronal cell proliferatory, antibacterial, anti‐diabetes, and anti‐osteoporosis properties .…”
Section: Introductionmentioning
confidence: 99%
“…1 The most typical triterpenic skeletons discovered in nature are the 6/6/6/5 tetracyclic scaffolds, 1b e.g., lanostane, dammarane, cucurbitane, and euphane (Figure S1), which are formed through rearrangement of triterpenic cations via different hydrogen shifts and methyl migrations. 2 A number of triterpenoids with uncommon 6/6/6/6 tetracylic framworks have also been reported, 3 including baccharane, D:B-friedobaccharane, lemmaphyllane, shionane, and montecrinane (Figure S1), which are actually 16(17→20)-abeo-rearranged triterpenoids with an expanded six-membered D-ring, 2 but they are still characterized by their eight methyl groups, as the skeletal cyclizations rarely occur on these nonactivated methyl groups. The only exception is cycloartane (Figure S1), of which methyl-19 is involved in the cyclization during skeletal formation.…”
mentioning
confidence: 99%
“…The only difference between the two compounds was that the methoxyl group at C-25 in 1 was replaced by a hydroxyl group The structure of 2 was accordingly identified as shown in Figure 1 and was named colqueleganoid B. Although many tetracyclic triterpenic skeletons including a number of 6/6/6/6-fused scaffolds have been discovered, 3,12 they are completely different from that of compounds 1 and 2.…”
mentioning
confidence: 99%